Animal genetic resources and sustainable livelihoods - Anderson, S. (Elsevier, 2003)
Many of the world's poor depend directly upon genetic, species and ecosystem biodiversity for their livelihoods. In many regions animal genetic resources (AnGR) are a vital component of this biodiversity. An estimated 1.96 billion people rely on livestock to supply part, or their entire daily needs. Complex, diverse and risk-prone peasant livelihood systems need AnGR that are capable of performing the functions required of them in these systems—AnGR that are flexible, resistant and diverse. In order to assess the importance of AnGR, as distinct from livestock per se, for sustaining and improving the livelihoods of the poor, the factors that differentiate between species and breeds in terms of the functions that animals fulfil in livelihoods and household economies need to be better understood. Central to this is the need to understand the functions of livestock as household assets, the full set of purposes the poor have in investing resources in livestock keeping, and the genetic traits that are important for the fulfilment of these purposes. If AnGR conservation is to make a contribution to improving the livelihoods of poor livestock keepers, the relative importance of AnGR from the livestock keepers’ perspective should be appraised. Then ways of maintaining and enhancing AnGR best suited to improving the livelihoods of the poor and ensuring equitable access to these resources can be addressed.